Pengaruh Price, Promotion, dan Trust terhadap Purchase Intention pada Online Shopping Festival di Aplikasi Shopee - Airlangga Raka Putra; Jatmiko Jatmiko (STIKes Ibnu Sina Ajibarang, 2024)
The newfound enthusiasm for online shopping has currently transformed the societal paradigm of shopping. Previously, individuals had to visit sellers in person before acquiring the desired items through conventional methods. One of the E-Commerce platforms used by the Indonesian society is the Shopee shopping application. With the Shopee platform, Indonesian consumers have the flexibility to shop anytime and anywhere, with a diverse range of product choices without needing to visit sellers directly. This makes it easier for Indonesian consumers to generate purchase intention. The aim of this study is to delve deeper into promotional strategies that can induce purchase intention among consumers, thereby enabling Shopee to maintain its position stability in the market. The sample in this study consists of 155 respondent selected using purposive sampling technique. Subsequently, the data were processed using multiple regression analysis methods. The results obtained from the testing indicate that, partially, price, promotion, and trust have a positive influence on purchase intention.